1998
DOI: 10.3109/07853899809029934
|View full text |Cite
|
Sign up to set email alerts
|

Sleep-disordered breathing in children

Abstract: The first series of children with obstructive sleep apnoea syndrome was reported in 1976. Later it became apparent that children may have breathing disorders during sleep without frank apnoea or 'hypopnoeas'. This pattern could be detected by measuring the oesophageal pressure. This led to the concept of sleep-disordered breathing as a spectrum that combines obstructive sleep apnoea syndrome and the upper airway resistance syndrome. Studies that do not take into account this spectrum may misclassify symptomati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
77
0
13

Year Published

2002
2002
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 107 publications
(92 citation statements)
references
References 39 publications
(3 reference statements)
2
77
0
13
Order By: Relevance
“…findings) and who also presented enlarged palatine tonsils (grade II or higher) 7 . Children presenting craniofacial abnormalities and neurological disorders were excluded from this study, as well as those patients referred to surgery to treat recurrent tonsillitis.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…findings) and who also presented enlarged palatine tonsils (grade II or higher) 7 . Children presenting craniofacial abnormalities and neurological disorders were excluded from this study, as well as those patients referred to surgery to treat recurrent tonsillitis.…”
Section: Methodsmentioning
confidence: 99%
“…Other important consequences are associated with developmental abnormalities, behavioral disorders, poor school performance and cor pulmonale 6,7 . Although the indications for adenotonsillectomy are well established, there are few studies about the impact of surgery in the quality of life of patients 8 .…”
Section: Introductionmentioning
confidence: 99%
“…1,2,13 study also showed that although polysomnograhy provides much information about OSDs, it is unable to establish the degree of quality of life improvement following adenotonsillectomy, as perceived by parents.…”
Section: Discussionmentioning
confidence: 99%
“…It is estimated that up to 3% of children have OSAHS, 1 and that a higher percentage has UARS. 2 OSDs cause a variety of physical conditions and affect the child's quality of life, leading to low weight gain, altered cranio-facial development, [3][4][5] cardiopulmonary sequelae, 3,4 behavioral changes, 3,4,6,7 and poor school performance, 8 all of which have been well documented. Thus an early diagnosis and treatment of OSDs in pediatric patients is paramount to revert or avoid these conditions.…”
Section: Introductionmentioning
confidence: 99%
“…19 This condition is called upper airway resistance syndrome. The clinical significance of upper airway resistance syndrome remains controversial and is under investigation.…”
Section: Polysomnographymentioning
confidence: 99%